Review of the Monograph “Canon Law in the Kingdom of Bohemia in the Middle Ages” - Gagas, Ignas (Teisė, 2024)
Krafl Pavel (2024). Canon Law in the Kingdom of Bohemia in the Middle Ages. Vydavatelstvo Z. Magdova–Tlaciaren s.r.o., Presov.
Keywords: -